ESTIMASI NILAI PEMULIAAN DAN MPPA (Most Probable Producing Ability) KUDA PACU BERDASARKAN SIFAT KECEPATAN LARI - Suryana, Muh. M.; Takaendengan, B.J.; Paputungan, umar; Pudjihastuti, E. (ZOOTEC, 2020)
ESTIMATION BREEDING VALUE AND MPPA (Most Probable Producing Ability) OF RACEHORSES BASED ON NATURE OF RUNNING SPEED. The aim of this study was to obtain the estimated number of breeding values from the racehorses parent in Minahasa for racehorse selection based on the superiority of genetic traits of speed. The descriptive analysis such asaverage, standard deviation and coefficient of variation of the speed and performance were done as the first step. Heritability, ripitability and the probability of breeding value (PBV) were calculated after all. The results of this study indicate that the value of heritability and repeatability obtained varies from low to high. The highest estimation of breeding value (PBV) for male (H), the highest MPPA (Most Probable Producing Ability) value in the population (individual B010) and the average MPPA value for the entire population were 0.0869, 0.1845 and 0.0239 respectively. The conclusion of this study puts the racehorse with the name "Swift Jhon" and "Super Princes" as males and individuals who have an average increase in the nature of the highest running speed.Â Keywords: Racehorse, Speed, EBV, MPPA